Burkholderia pseudomallei in soil and natural water bodies in rural Sri Lanka: A hidden threat to public health - Jayasinghearachchi, Himali S.; Muthugama, Thilini A.; Masakorala, Jayanthi; Kulasekara, Upeksha S.; Jayaratne, Kumari; Jayatunga, D. A. Dasun N.; De Silva, Aruna D.; Corea, Enoka M. (Frontiers in Veterinary Science, 2023)
Burkholderia pseudomallei is the causative agent of the potentially fatal infection, melioidosis. This study provides the first evidence for the presence of B. pseudomallei in soil and water in Sri Lanka. Targeted sampling of soil and natural water sources was done between November 2019 and October 2020 over six field visits encompassing the neighborhood of 25 culture and/or antibody-positive melioidosis patients in northwestern, western and southern Sri Lanka. A total of eight environmental isolates of B. pseudomallei (BPs-env1 to BPs-env8) were cultured from 116 soil and 117 natural water samples collected from 72 locations. The presence of B. pseudomallei in soil and natural water in these areas poses a risk of melioidosis for populations cultivating crops in such soils and using untreated water from these sources for drinking, bathing and other domestic purposes. Identifying sites positive for B. pseudomallei may help to mitigate risk by raising public awareness of contaminated environmental sources and allowing soil and water remediation.